Stepping stones versus dead end jobs: Exits from temporary contracts in Italy after the 2003 reform - Giovanni S. F. Bruno; Floro Ernesto Caroleo; Orietta Dessy (Institute for the Study of Labor (IZA), 2012)
In this paper we study labor market transitions out of temporary jobs in Italy focussing on an interesting period of the Italian recent history: the one immediately following the last labor market reform aimed at flexibilizing and liberalizing the Italian labor market by a widespread use of temporary work arrangements in 2003, and immediately preceding the economic downturn starting in the second half of 2007. The data-set used is the 2004-2007 IT-SILC individual panel. We apply a discrete-time duration analysis and estimate a competing-risk model for assessing to which extent, and for whom, starting a temporary job after 2004 results within a 3-years span in a stepping stone to permanent employment rather than a dead end out of the labor market or in precarious jobs. We find that temporary contracts have a positive impact only on men's transitions to permanent employment. School leavers, workers in the South, as well as women, are instead rather penalized after a temporary job. They have an higher probability to remain trapped in temporary contracts than men and an higher probability of exiting the labour market. In particular, school leavers entering the labour market with a temporary contract experience relatively high exit-rates to non-employment just after the first year of the contract.
Keywords: J24; C41; C33; C35; J6; 330; mixed multinomial logit; discrete duration data; temporary jobs; Befristeter Arbeitsvertrag; Berufliche Integration; Arbeitsmarktflexibilität; Schätzung; Italien